Modeling Life Expectancy Index in West Nusa Tenggara Province with Panel Regression Method - Astuti, Alfira Mulya; Ashri, Erina Salsabila; Sabri, Sabri (Inferensi, 2024)
Health is a condition of total physical, mental, and social well-being, rather than simply the lack of disease or weakness. One way to assess health indicators in a region is by enhancing the development of the health sector, which may be quantified using the life expectancy index (LEI). This study seeks to analyze the impact of average years of schooling, the adjusted per capita expenditure, and the number of poor people on life expectancy in NTB province from 2011 to 2020. The study's individual observation units consist of 10 regencies/cities in NTB Province. The data were obtained from BPS NTB in a panel data format and processed using the panel regression method. The panel model selection indicates that the Random Effect Model is the most suitable to predict the life expectancy in NTB province. The average years of schooling and the adjusted per capita expenditure have a notable impact on the life expectancy in NTB province. The effect provided is a beneficial impact. The number of poor people has a limited impact on life expectancy. Simultaneously, the average years of schooling, the adjusted per capita expenditure, and the number of poor people in the province of NTB have a substantial impact on the life expectancy.